Kinematic analysis of forehand drop shot and long shot services in table tennis / Norzuria Ibrahim - Norzuria , Ibrahim (2020)
Table tennis is one of the most widely played sports in the world. A frequent hand movement is compulsory to execute stroke than other limbs, especially the projection of racket and ball speeds,which can help to improve players’ performance. Until now, research on table tennis serving is limited. Service was assumed important in table tennis because the effective serve may allow the serving player to have advantage and control over the game. The 3D dynamic analysis is the appropriate method to analyze a sport activity such as table tennis. Therefore, the aim of research was to determine the kinematic involved in arm segment rotations towards horizontal ball and racket head velocities during forehand service in table tennis. Yamaguchi’s kinematic model is one of methods to analyze arm segment motion. However, the equations in Yamaguchi’s model were not completed since only developed the model until proximal end of segment. Furthermore, the value of specific positions at arm segment in the model remained unknown. Thus, the present study has improved the Yamaguchi’s kinematic model by adding some parameters (calculation of velocity until COM of segments and obtained the value of specific positions at arm segment) to complete the model and can be used to analyze table tennis serving motion. Twenty six participants were selected to participate in this research. The study captured radiography images of 10 participants to obtain the value of positions at arm segment. Furthermore, 16 collegiate table tennis players were selected to perform forehand drop shot and long shot services. Five infrared cameras operating at 250 Hz were used to record the table tennis serving motion. Radial deviation angular velocity was significantly correlated with racket velocity (rs = 0.638, P < 0.05) and ball velocity during drop shot service (rs = 0.647, P < 0.05). Racket velocity at impact exhibited a significant correlation with radial deviation (r = 0.803, P ˂ 0.05) and wrist palmar flexion angular velocities (r = 0.737, P < 0.05) during long shot service. The shoulder flexion and shoulder internal rotation velocities were significantly different between long shot and drop shot services (p = 0.001, p = 0.005). The amplitude of the graph during long shot service (Figure 4.6) was less sharp compared to the graph during drop shot service particularly in shoulder internal rotation, elbow flexion and wrist palmar flexion which revealed that players played both services with the same posture at different speed. Furthermore, the change in shoulder flexion and shoulder internal rotation at impact will distinguished between drop shot and long shot services. Moreover, it was concluded that increasing radial deviation will increase racket and ball velocities at impact during drop shot service. Increasing the radial deviation and wrist palmar flexion will increase racket head velocity at impact during long shot service. However, the ball velocity at impact could not be influenced by the arm segment rotations and racket speed during long shot service. Focusing on the recommendations above during training may allow the players to gain advantage over the game.